Histoplasmose disseminada em pacientes portadores de HIV/AIDS: tratamento de consolidação em hospital de referência do Ceará - Almeida Júnior, Antônio Mauro Barros (2020)
Histoplasmosis is a fungal disease caused by Histoplasma capsulatum. The State of Ceará in Northeastern Brazil has one of the highest prevalence, relapse, and death rates in the world due to the disease in Acquired Immunodeficiency Syndrome (AIDS) patients. Currently, the treatment of this mycosis in HIV patients is carried out in three stages: induction, consolidation, and secondary prophylaxis. For consolidation therapy, itraconazole (400mg daily) as the first-choice drug is recommended for a minimum fixed period of 12 months. Recently, a document published by the World Health Organization recommended reducing such period to six months, depending on defined criteria. The one-year consolidation phase has been the target of criticism on account of hindering patient adherence and favoring abandonment, in addition to increasing the risk of drug interactions and adverse effects. The present study aimed to investigated adherence, duration and drug interactions in the consolidation phase of DH treatment in AIDS patients at the Hospital São José of Infectious Diseases (HSJ), a reference in infectious diseases in the State of Ceará. Data collection was conducted by reviewing the medical records of DH/AIDS patients treated at the HSJ, from January 2010 to January 2015. The study included 32 patients who continued consolidation therapy and were followed-up at the HSJ outpatient clinic. The median age was 31.5 years (IQR = 26.5-38.5) and the majority were male (87.5%). Among the antifungal treatment withdrawals for known reasons, 25.9% (7/27) were due to patient abandonment. The median duration of itraconazole use in those who maintained the consolidation dose for up to six months was only 100 days (IQR = 64 - 161) and for those who used itraconazole for more than six months, it did not reach one year (341 days, IQR = 238 - 392; p = 0.09). No deaths were observed in either group. In 59.1% (13/22) of the patients, the nonnucleoside analogue reverse transcriptase inhibitors (NNRTIs) remained a component of highly active antiretroviral therapy (HAART), along with the consolidation phase of DH treatment. In this group, only one relapse was reported, although it occurred in a patient who did not use HAART regularly. The interaction between itraconazole and NNRTI was not significant and the appearance of adverse effects was not a relevant factor for the abandonment of DH consolidation treatment. The risk associated for relapse in DH/AIDS patients in the present study was the lack of immune recovery. The regular use of HAART, combined with immune recovery, showed to be more effective than long periods of consolidation to prevent relapses due to DH in AIDS patients.